Exploring innovative apprenticeship: quality and costs - Grollmann, Philipp [Verfasser]; Rauner, Felix [Verfasser] (My University, 2007)
The purpose of this paper is to show that the quality of learning in German apprenticeships can be increased without raising costs under certain conditions. It starts with a contextual description of apprenticeship in the dual system, showing that this insight is of central importance, since employers in Germany are increasingly withdrawing from apprenticeship provision. The paper is a case study-methodology and shows one selected case out of 24 presented. The selected case is then related to the findings of the other cases explored. The findings in the paper imply that quality of apprenticeships can be improved without an increase in costs, challenge the classical economics of apprenticeship. "Grounded" indicators of quality in apprenticeship are formulated: learning in productive work processes is a core characteristic of apprenticeships; the productive work apprentices engage in needs to follow a well thought through sequential logic; learning is based on a high degree of autonomy; learning is embedded into the business process; client satisfaction provides an important quality benchmark; commitment to occupation and the company can provide a source of responsibility and quality; and professional competence is the ultimate goal of learning. The paper suggests an intensified integration of apprenticeship training into productive work processes. In order to turn this into quality learning the complexity of tasks needs to be increased over the course of apprenticeship. (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; L 6 Qualität; S 4.3.6 Human Capital; Berufsausbildung; Duales System; Kosten-Nutzen-Relation; Qualität; Indikatoren; Lernprozess; Prozessorientierung; Handlungsorientierung; Humankapital; Bildungsertrag